HUBUNGAN PENYAKIT PENYERTA DENGAN DEPRESI PADA LANSIA DIABETES MELLITUS - Ridho Akbar Firdaus; Savitri Gemini; Laeli Mufidah (Ensiklopedia of Journal, 2026)
This study examines the relationship between comorbidities and depression in elderly patients with diabetes mellitus at Puskesmas Sei Langkai, Batam. The background highlights high cases of elderly diabetes mellitus (3,064 cases/4.93%) and elderly depression (52 cases/0.02%) in 2023, where comorbidities can increase depression risk, impacting physical, psychological, and social aspects. Method:A quantitative study with cross-sectional design involving 54 elderly samples selected through purposive sampling. Data were collected using questionnaires and analyzed with the Kruskal-Wallis test. The majority of respondents (79.6%) had comorbidities, with hypertension being the highest (77.8%). About 63% suffered from diabetes mellitus for 2 years. Statistical tests showed a significant relationship between comorbidities and depression (p=0.0490.05). Comorbidities increase the health burden on elderly diabetes mellitus patients and correlate with depression occurrence. These findings emphasize the importance of comprehensive health monitoring in the elderly, particularly detection and management of comorbidities to prevent or reduce depression risk. This information is useful for elderly patients and their families in holistic healthcare efforts.Keywords: Comorbidities, Depression, Diabetes Mellitus